AMYOBA DIZENTERIYASI, PARAGEMOLITIK, NAG -VIBRIONLAR, TIBBIYOT AMALIYOTIDAGI AHAMIYATI VA BAKTERIOLOGIK DIAGNOSTIKASI - Umida Esirgapova Xasanovna; Rajabova Azizabo (TADQIQOTLAR, 2026)
Abstract This research provides an extensive academic and clinical inquiry into the microbiological characteristics and diagnostic protocols of amoebic dysentery and non- cholera vibrios, specifically Vibrio parahaemolyticus and NAG-vibrios. The study evaluates the etiological significance of Entamoeba histolytica in gastrointestinal pathology and its potential for extraintestinal complications, such as hepatic abscesses. Furthermore, it examines the emerging public health threat posed by halophilic vibrios in the context of foodborne infections. By analyzing contemporary bacteriological, serological, and molecular diagnostic methodologies, the article highlights the critical importance of precise laboratory identification in clinical practice. The findings emphasize that differential diagnosis is essential for effective therapeutic intervention and the prevention of widespread epidemiological outbreaks.